Mitigation of corrosion attack on carbon steel coated cermet alloy in different anion contents - Mohd Khalid, Muhamad Azrin; Ismail, Azzura (AIP Publishing, 2017)
This research study evaluated the corrosion mechanism attack on carbon steel coated with cermet alloys (WC9% Ni) in seawater at different sulphate-to-chloride ratios. The four different sulphate-to-chloride ratios were synthesised with the same seawater salinity of 3.5 % and same pH of real seawater. The corrosion tests involved immersion and electrochemical tests. The immersion test is used to determine the cermet coating ability to withstand the corrosion attack based on different ratios of anions present in the seawater at different periods of immersion. The corrosion attack was characterized by optical and Scanning Electron Microscopy (SEM). The aggressive anions present in the seawater influenced the corrosion attack on the cermet coating. For immersion test, results revealed that increasing sulphate more than chloride, increased the weight loss of cermets. The electrochemistry analysis showed that the passive layer forms on cermet coating prevented the material from further corrosion attack. However, due to its porosity, the passive layer collapsed and exposed the material for other corrosion reaction. For electrochemical test, the result shows that the solution with sulphate-to-chloride ratio of 0.14 (real seawater) has the highest corrosion current and Open Circuit Potential (OCP) compared to other solutions (different sulphate-to-chloride ratio). In conclusion, sulfate and chloride show their competition to attack the cermet coating on carbon steel and the higher the amount of chloride present in seawater, the higher the corrosion rate and pits formed on the cermet coating.